Development of Indirect Competitive ELISA and Visualized Multicolor ELISA Based on Gold Nanorods Growth for the Determination of Zearalenone - Tianyu Ma (MDPI AG, 2021)
In this study, a zearalenone (ZEN) hapten was designed and prepared against the mycotoxin ZEN, and the original coating ZEN-ovalbumin (ZEN-OVA) was prepared by conjugation with OVA. Based on the gold nanorods (AuNRs) of uniform size and stable properties synthesized by the seed-mediated method, the indirect competitive enzyme-linked immunosorbent assay (ic-ELISA) and the AuNRs growth-based multicolor ELISA for detecting ZEN toxin were further established. Under the optimal experimental conditions, the coating amount of ZEN-OVA: 0.025 μg/well, antibody (Ab) dilution factor: 32,000 times, blocking solution: 0.5% skimmed milk powder, enzyme-labeled secondary Ab diluted 10,000 times, and a pH of the PBS buffer at 7.4, the sensitivity (IC50) of the established ic-ELISA for ZEN detection reached 0.85 ± 0.04 μg/L, and the limit of detection (IC15) reached 0.22 ± 0.08 μg/L. In the multicolor ELISA based on the growth of AuNRs, as the content of ZEN increased, the mixed solution exhibited a significant color change from brownish red to colorless. ZEN concentration as low as 0.1 μg/L can be detected by the naked eye (brown red to dark gray). This study provided an effective analysis strategy for the rapid screening and accurate monitoring of the ZEN contaminant in foods.